"Going Out" and Going In-House: Chinese Multinationals' Internal Legal Capacity in the United States. Issue 2 (29th May 2021) - Li, Ji
Abstract : The "in-house counsel movement" of the past few decades, with its far-reaching implications for the legal profession, the legal service market, and corporate governance, has attracted a great deal of academic attention. Few scholars, however, have examined the global expansion of emerging market companies and their in-house legal capacity. To narrow the gap, this article investigates the in-house legal capacity of Chinese firms in the United States. In doing so, it focuses on two important yet underexplored questions: (1) whether and how institutions in China influence the capacity building; and (2) whether the Chinese investors' ownership structure makes a difference in that regard. By analyzing a unique set of survey data and 122 interviews with lawyers, in-house counsel, and business executives, this article uncovers evidence of both multi-institutional influence and state-ownership effects. The findings contribute to theoretical and policy debates about the legal profession, the legal service market, and the ramifications of expanding Chinese multinational companies.